2023
DOI: 10.2147/ndt.s403002
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Related Depression and Anxiety: A 22-Year Bibliometric Analysis (2000-2022)

Abstract: Background Parkinson’s disease (PD) is one of the common neurodegenerative diseases. Depression and anxiety are the most common psychiatric symptoms of PD. It is important to study the potential relationship between PD and depression or anxiety. Aim This study aimed to use bibliometrics to analyze the papers about parkinson’s disease related depression and anxiety over the last 22 years, and to characterize the current status of research and predict future hotspots. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…While the primary clinical manifestation of PD is motor symptoms, non-motor symptoms like anxiety and depression are also the most common and significant psychiatric features of PD ( Landau et al, 2016 ). Moreover, these two symptoms often accompany PD patients and may persist throughout the disease course ( Zhang et al, 2023 ). In addition, cognitive deficits related to learning and memory abilities have been observed in more than 15% of PD patients ( Svenningsson et al, 2012 ).…”
Section: Research On Non-depressive Conditionsmentioning
confidence: 99%
“…While the primary clinical manifestation of PD is motor symptoms, non-motor symptoms like anxiety and depression are also the most common and significant psychiatric features of PD ( Landau et al, 2016 ). Moreover, these two symptoms often accompany PD patients and may persist throughout the disease course ( Zhang et al, 2023 ). In addition, cognitive deficits related to learning and memory abilities have been observed in more than 15% of PD patients ( Svenningsson et al, 2012 ).…”
Section: Research On Non-depressive Conditionsmentioning
confidence: 99%
“…The HAMD 35 is a scale for the diagnosis of depression. Given the prevalence of co-occurring anxiety and depression among patients with PD, 36 it is indeed valuable to incorporate HAMD to gauge the severity of depression. This approach allows you to explore potential correlations between anxiety, depression and the effectiveness of acupuncture.…”
Section: Outcome Measurementioning
confidence: 99%
“…It also leads to impairment of cognition and mood. [42] One study showed significant improvements in proprioception, motion range, and quality of life for Parkinson's patients through rebound therapy compared to treadmill running. [43] However, evidence supporting its effectiveness is limited, and further trials, such as the Lisbon Intensive Falls Trampoline Training study, are required.…”
Section: Balancementioning
confidence: 99%